2021
DOI: 10.1039/d0ta12332c
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer ceramic film capacitors for high-performance energy storage: progress and outlook

Abstract: The dielectric capacitors, which has the characteristics of greater power density, have received extensive research attention due to its application prospects of pulsed power devices. Film capacitors are easier to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 138 publications
0
22
0
Order By: Relevance
“…When the external electric field is withdrawn, the dielectric depolarization allows the accumulated free charges on the electrode to be rapidly released. 63 The hysteretic response of P to E causes partial energy loss, 64 and the discharging efficiency (Z) can be calculated from the energy loss and charged energy density. Fig.…”
Section: Energy Storage Performancementioning
confidence: 99%
“…When the external electric field is withdrawn, the dielectric depolarization allows the accumulated free charges on the electrode to be rapidly released. 63 The hysteretic response of P to E causes partial energy loss, 64 and the discharging efficiency (Z) can be calculated from the energy loss and charged energy density. Fig.…”
Section: Energy Storage Performancementioning
confidence: 99%
“…Nowadays, dielectric thin‐film capacitors, which can store and release ultralarge energy densities in an extremely short time, are extensively investigated for applications in pulsed‐power electronic systems. [ 1–5 ] Such systems are used in many application fields, ranging from medical devices (such as pacemakers and defibrillators), consumer or industrial systems (camera flash, oil and gas exploration), transportation (hybrid electric vehicles), and in military applications (radar and high‐power microwave devices). [ 1,4–8 ] Recent studies focused on the enhancement of the energy‐storage density of dielectric thin‐film capacitors by using advanced materials and novel device architectures, [ 9,10 ] employing also ferroelectric (FE), antiferroelectric (AFE), or relaxor‐ferroelectric (RFE) materials.…”
Section: Introductionmentioning
confidence: 99%
“…
Such systems are used in many application fields, ranging from medical devices (such as pacemakers and defibrillators), consumer or industrial systems (camera flash, oil and gas exploration), transportation (hybrid electric vehicles), and in military applications (radar and high-power microwave devices). [1,[4][5][6][7][8] Recent studies focused on the enhancement of the energy-storage density of dielectric thin-film capacitors by using advanced materials and novel device architectures, [9,10] employing also ferroelectric (FE), antiferroelectric (AFE), or relaxor-ferroelectric (RFE) materials. In general, it is found that a large difference between maximum polarization (P m ) and remanent polarization (P r ), and a high electric breakdown field/breakdown strength (E BD ) are beneficial for high energy-storage densities.
…”
mentioning
confidence: 99%
“…More recently, several improvements have been put forward to regulate the P – E characteristics of the ferroelectric film for capacitive energy storage, including defect, dead-layer engineering, strain, doping, multilayer, and process control. ,, For instance, rare-earth La-doped Bi 5 Ti 3 FeO 15 thin films induced relaxation behaviors and inhibited grain growth that achieved a large W rec and a high η . Consequently, reducing the grain size of the materials is a validly avenue for improving energy storage performances because of enhanced E b ( E b ∝ 1/√ G , G is grain size).…”
Section: Introductionmentioning
confidence: 99%